ESKALASI DAYA TARIK MEDIA PEMBELAJARAN TEKS PROSEDUR BERBASIS KONTEN VIDEO PENDEK PADA SOSIAL MEDIA TIKTOK - ermira np (STKIP PGRI SUMENEP, 2022)
Abstract The era of globalization causes humans to be unable to be separated from technology, especially in the realm of education. To increase the attractiveness of Indonesian language learning media by utilizing short video content on TikTok social media. The aims of this study are (1) to explain the escalating form of TikTok's social media appeal for learning Indonesian language and literature, and (2) to describe the linguistic form of procedure text based on short video content on TikTok social media as a learning medium. The data collection technique used tapping techniques and advanced techniques, including free-to-talk. Researchers looked at five short video content from five different creators. This research utilizes the type of data analysis in the form of content analysis. The linguistic rules contained in the five contents are: (1) temporal conjunctions, (2) imperative sentences, (3) material verbs, (4) human participant sentences, (5) sequence marker numbers and (6) degree/degree descriptions. quantity. In addition, the number of account followers, the number of likes, comments, and how many videos are shared is one of the implied forms of the success of learning media by utilizing social media TikTok. Keywords: learning media; procedure text; tiktok